A NEW PERSPECTIVE ON AL-JUMLAH ISMIYAH AND FI'LIYAH IN THE CONTEXT OF AL-QAWAID AL-ASASIYAH FI ULUMIL QURAN BY SAYYID MUHAMMAD ALAWY AL-MAKKY - Basid, Abdul (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2023)
This article aims to provide a reinterpretation of the concepts of Al-Jumlah Ismiyah and Fi'liyah in the light of the book